1983
DOI: 10.1136/ard.42.5.494
|View full text |Cite
|
Sign up to set email alerts
|

Heat distribution over normal and abnormal joints: thermal pattern and quantification.

Abstract: SUMMARY We have identified regular thermal patterns over normal knee, ankle, and elbow joints and demonstrate how synovitis affecting these joints may be identified by alteration or loss of the thermal pattern. Sixty healthy volunteers were thermographed on a total of 190 occasions, and 614 out of 618 joints conformed to the normal thermal pattern. Eight-five patients with synovitis of at least one of the specified joints were thermographed on a total of 339 occasions, and 322 out of 1362 thermograms were abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
1
3

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 10 publications
1
50
1
3
Order By: Relevance
“…Classicamente, há dois índices para avaliação da atividade inflamatória por imagem IR: o índice termográfico (TI), que é a análise multi-isotérmica com base na temperatura cutânea média de uma área articular pré-definida (ROI) (3) , e o índice de distribuição térmica (HDI), com base em ± 1 desvio-padrão (DP) da temperatura cutânea média dessa ROI (31) . Os valores do TI das articulações periféricas normais variam entre 0,35 e 2,30, com uma média de 1,20.…”
Section: Artrite Reumatóideunclassified
See 1 more Smart Citation
“…Classicamente, há dois índices para avaliação da atividade inflamatória por imagem IR: o índice termográfico (TI), que é a análise multi-isotérmica com base na temperatura cutânea média de uma área articular pré-definida (ROI) (3) , e o índice de distribuição térmica (HDI), com base em ± 1 desvio-padrão (DP) da temperatura cutânea média dessa ROI (31) . Os valores do TI das articulações periféricas normais variam entre 0,35 e 2,30, com uma média de 1,20.…”
Section: Artrite Reumatóideunclassified
“…Salisbury et al avaliaram 85 pacientes com evidência clínica de sinovite em pelo menos uma articulação. De 1.362 termogramas, incluindo articulações sadias, todos os 322 com padrão alterado na distribuição térmica apresentavam sinovite clinicamente (31) . Porém, como ressalta Thumb (44) , nada substitui um experiente reumatologista, uma vez que o diagnóstico da AR é clínico e nenhum exame isolado é diagnóstico.…”
Section: Artrite Reumatóideunclassified
“…It is a picture of autonomic dysfunction which seems to correlate well with regions of pain (Boas, 1964;Salisbury et al, 1983;Spalding et al, 2008). Pain felt at the area of injury is generally seen to be hyperthermic (increased thermal emission) due to decreased sympathetic function and alpha receptor blockage from metabolic by-products such as substance P, kinins, histamines, and so on (Bjorkstrom and Goldie, 1980;Fernandez-Duenas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of veterinary medicine, where localization of pain sometimes is not possible, the IR diagnostic system, used in combination with a clinical examination and additional imaging modalities, provides highly effective results by pinpointing areas of suspicion (Brenner et al, 2006;Craciunescu et al, 2009;Infernuso et al, 2010;Kastberger et al, 2003;Poljak-Blazi et al, 2009;Stubsjoen et al, 2009). In human medicine, thermography has already been effectively used for non-invasive assessment of disease activity in osteoarthritis of the knee, hands and the tempomandibular joint (Boas, 1964;Fikackova and Ekberg, 2004;Salisbury et al, 1983;Selfe et al, 2006;Spalding et al, 2008), as well as in rheumatic arthritis (Boas, 1964;Brenner et al, 2006;Salisbury et al, 1983;Spalding et al, 2008), scleroderma, Raynaud´s disease (Chikura et al, 2010;Schlager et al, 2010), frozen shoulder or rotator cuff tendinitis (Vecchio et al, 1992), breast cancer (Arora et al, 2008;EtehadTavakol et al, 2010;Gescheit et al, 2010;Ng, 2009), reflex sympathetic dystrophy (Bruehl et al, 1996;Krumova et al, 2008;Niehof et al, 2008), sexual dysfunction (Seeley et al, 1980;Smith et al, 2009) and for the evaluation of patellofemoral arthralgia (kneecap pain) in athletes (Devereaux et al, 1986). However, in spite of being a reliable method for objective pain evaluation (Friedman, 1994;Han et al, 2010;Leclaire et al, 1996;Niehof et al, 2006;Pawl, 1991;…”
Section: Introductionmentioning
confidence: 99%
“…Binder et al (1983) and Salisbury et al (1983) both demonstrated higher T sk in diurnal assessments when using IRT.…”
mentioning
confidence: 99%